The Influence of Leader-Member Exchange on Employee Performance With Job Satisfaction As A Mediating Variable At Harris Barelang Batam - Laura Maharani; Khairani Saladin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of leader-member exchange on employee performance with job satisfaction as a mediating variable at HARRIS Barelang Batam. A quantitative approach with a causal associative design was employed, using a saturated sampling technique involving 52 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that leader-member exchange does not have a significant direct effect on employee performance. However, leader-member exchange has a significant effect on job satisfaction, and job satisfaction significantly influences employee performance. Furthermore, job satisfaction fully mediates the relationship between leader-member exchange and employee performance. These findings suggest that improving employee performance through leader-member exchange requires an initial enhancement in job satisfaction.